2009
DOI: 10.1111/j.1526-4610.2009.001460.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Review and Epidemiology of Headache Disorders in US Service Members: With Emphasis on Post‐traumatic Headache

Abstract: Migraine or headache is a common problem in the active duty population, in the recently deployed service members, and is a cardinal symptom of traumatic brain injury. While there is increasing appreciation of the clinical burden of post-traumatic headache (PTHA) in the military traumatic brain injury population, there remain significant research gaps related to the epidemiology of PTHA, including lack of understanding of natural history, whether there are predisposing factors that predict the development or pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 19 publications
1
23
0
1
Order By: Relevance
“…Of those without acute posttraumatic headache, 25% developed delayed onset of CDH. The study does point out the difficulty of identifying those with posttraumatic CDH as a group [17,Class III]. In a study from the civilian population, Couch and Bearss [18,Class III] found that less severe head injury was more likely to lead to CDH, although there is controversy on this point.…”
Section: Clinical Aspectsmentioning
confidence: 97%
See 1 more Smart Citation
“…Of those without acute posttraumatic headache, 25% developed delayed onset of CDH. The study does point out the difficulty of identifying those with posttraumatic CDH as a group [17,Class III]. In a study from the civilian population, Couch and Bearss [18,Class III] found that less severe head injury was more likely to lead to CDH, although there is controversy on this point.…”
Section: Clinical Aspectsmentioning
confidence: 97%
“…Recent articles dealing with chronic headache in soldiers returning from deployment to war zones in Iraq and Afghanistan have suggested that the prevalence of posttraumatic headache attributed to mild head injury is as high as 37% [15][16][17]Class III]. In a recent study, 5,270 soldiers were screened for mild traumatic brain injury at a post-deployment evaluation; 1,033 (19.6%) met criteria for concussion, and 98% of these had headaches at the time of screening.…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…A smaller study of returning Iraq and Afghanistan veterans did use International Classification of Headache Disorders criteria, and found a greater likelihood of migraine (which has photophobia as a diagnostic criterion) in veterans with more frequent injuries and abnormal findings on neurological and neuropsychological exams (39). Clearly, these data are not conclusive, and they speak to the need for more precise ascertainment of both photophobia and headache symptoms after TBI (40). …”
Section: Conditions Associated With Photophobia (Table 1)mentioning
confidence: 99%
“…The incidence of head trauma is about 180 to 220 per 100,000 people in North America and 350 per 100,000 people in Europe [9]. An interesting piece of data is that the severity of the head injury is inversely proportional to the occurrence of both acute and chronic PTH.…”
Section: Acute Posttraumatic Headachementioning
confidence: 98%